Short-term effects of the global economic and financial crisis on households in three developing countries: the cases of El Salvador, Tajikistan and Cambodia - Esther Gehrke (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The global economic and financial crisis affected countries all over the world. Although, poorer economies were on average less affected by the crisis, some developing countries still experienced considerable output losses. This paper shows that households living in developing countries were in a bad position to cope with the crisis. Worsening labour market conditions and decreased remittances reduced the welfare of many households, and the effects were particularly harsh for poor and vulnerable households. The absence of functioning social protection schemes in many developing countries made the situation even worse. This paper argues that promoting social cash transfers in developing countries could help protect their populations from the adverse consequences of economic shocks.
Keywords: 330; Armut und Ungleichheit; Internationales Finanzsystem; Soziale Sicherung und Inklusion